FACTORS CONTRIBUTING TO BANK STABILITY IN CHANNELIZED, ALLUVIAL STREAMS. (26th November 2012) - Davis, L.; Harden, C. P.
ABSTRACT Bank failure is a common fluvial process and can be a pervasive fluvial response to natural and anthropogenic disturbances. Previous research has identified causes and types of bank failure, but the conditions that lead to the cessation of bank failure remain poorly explained. This research examines differences between banks with active bank failure and banks that exhibit evidence of past bank failure that ceased (dormant) throughout three West Tennessee (USA) rivers to provide insight into the processes that cause bank failure to end. Bank characteristics were observed at 68 sites, and data from 55 banks were used to create a logistic regression model. Bank characteristics entered into the model included: vegetative cover, failure location, bar association, bank material, channel width‐to‐depth (w/d) ratio, and average bank angle. Results of the logistic regression suggest that bank angle best explains (p = 0.31 and odds ratio = 8.2) the difference between banks with active and dormant bank failure. Interestingly, vegetative cover and bank material composition, which have been found to be important in bank stabilization by previous researchers, were not significant predictors of bank stability according to the logistic regression model. These results suggest that in absence of drastic differences in bank material resistance (bedrock vs sediment): (1) spatial patterns of bank failure at the system‐scale will be diffuse, (2) bank stability can require a multiple decades, and (3) the potential for vegetation to stabilize banks may be limited in some alluvial systems because of positive feedbacks created by repeated human disturbance. Copyright © 2012 John Wiley & Sons, Ltd.